Sharīʿah non-compliant assets as rahn (pledge) in Islamic banking products: a fiqhī perspective - Lokmanulhakim Hussain; M. Mahbubi Ali (ISRA International Journal of Islamic Finance, 2017)
Purpose: The purpose of this study is to present a framework regarding the use of Sharīʿah non-compliant assets as rahn (pledge) and to provide the Sharīʿah analysis on the application of numerous collateral instruments, including financial assets such as shares, unit trusts, current accounts and investment accounts which are Sharīʿah non-compliant. Design/methodology/approach The study adopts a library-based approach to examine the concept and requirements of rahn, deliberate the classification of Sharīʿah non-compliant assets and delineate the Sharīʿah views on the use of Sharīʿah non-compliant assets as pledges. It also examines the various forms of pledge available and offered in the market using document analysis as well as through discussion with industry practitioners. Findings In general, the study concludes that Sharīʿah non-compliant assets, either due to their essence or due to the means of acquisition where there is no ownership from Sharīʿah perspective, cannot be used as rahn. This study also provides the Sharīʿah analysis on the use of modern instruments such as shares, unit trusts, current accounts, investment accounts and insurance policy as pledges. Originality/value The paper provides a reference source for regulators in formulating an appropriate policy and framework on Sharīʿah-compliant collateral; Sharīʿah committees of Islamic financial institutions in arriving at Sharīʿah decisions on collateral; and industry practitioners in establishing internal policies and procedures on collateral.
Keywords: 330; Collateral; pledge; rahn; Sharīʿah non-compliant asset